2019
DOI: 10.1038/s41388-019-0885-4
|View full text |Cite|
|
Sign up to set email alerts
|

UDP-glucose 6-dehydrogenase regulates hyaluronic acid production and promotes breast cancer progression

Abstract: An improved understanding of the biochemical alterations that accompany tumor progression and metastasis is necessary to inform the next generation of diagnostic tools and targeted therapies. Metabolic reprogramming is known to occur during the epithelial-mesenchymal transition (EMT), a process that promotes metastasis. Here, we identify metabolic enzymes involved in extracellular Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 29 publications
(38 reference statements)
3
42
0
Order By: Relevance
“…For example, knocking down UGDH expression or pharmacological scavenging of UDP-glucuronate through the glucuronidation pathway by 4-methylumbelliferone is sufficient to inhibit cellular invasion and colony formation in a breast cancer model, and the authors suggested that metabolic reprogramming to support epithelial-mesenchymal transition may require the shift to glucose metabolism because remodeling of the extracellular matrix involves upregulation of HA production. 53 In contrast, another study found that knocking down UGDH also reduced the migration of lung adenocarcinoma cells, but feeding back UDP-glucuronate and HA was insufficient to recover this effect, 54 suggesting it is not dependent on the UGDH product. Such apparently contrasting results may be partially reconciled by the finding that genetically and pharmacologically reducing HA precursor pools, UDP- N -acetylglucosamine and UDP-glucuronate, stimulates HA synthase 3 (HAS3) endocytosis, whereas excess UDP- N -acetylglucosamine caused vesicle recycling to the plasma membrane, promoted HAS3-positive extracellular vesicle shedding, and increased metastatic potential.…”
Section: Post-translational Regulation Of Ugdh and Pg Productionmentioning
confidence: 98%
“…For example, knocking down UGDH expression or pharmacological scavenging of UDP-glucuronate through the glucuronidation pathway by 4-methylumbelliferone is sufficient to inhibit cellular invasion and colony formation in a breast cancer model, and the authors suggested that metabolic reprogramming to support epithelial-mesenchymal transition may require the shift to glucose metabolism because remodeling of the extracellular matrix involves upregulation of HA production. 53 In contrast, another study found that knocking down UGDH also reduced the migration of lung adenocarcinoma cells, but feeding back UDP-glucuronate and HA was insufficient to recover this effect, 54 suggesting it is not dependent on the UGDH product. Such apparently contrasting results may be partially reconciled by the finding that genetically and pharmacologically reducing HA precursor pools, UDP- N -acetylglucosamine and UDP-glucuronate, stimulates HA synthase 3 (HAS3) endocytosis, whereas excess UDP- N -acetylglucosamine caused vesicle recycling to the plasma membrane, promoted HAS3-positive extracellular vesicle shedding, and increased metastatic potential.…”
Section: Post-translational Regulation Of Ugdh and Pg Productionmentioning
confidence: 98%
“…UGDH participates in tumour formation and cancer migration in breast cancer, colorectal carcinoma, glioblastoma and lung cancer. [11][12][13][14] Previous studies also demonstrated that UGDH is regulated by transforming growth factor-β pathway, including p38, extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK). Moreover, UGDH has been reported to regulate cell glycosaminoglycan (GAG) level by catalysing the conversion of UDP-glucose to UDP-glucuronate.…”
Section: Glycosphingolipid (Gsl) Is a Glycolipid On The Cell Membranementioning
confidence: 99%
“…UDP‐glucose dehydrogenase (UGDH) is an enzyme that catalyses NAD + ‐dependent two‐step oxidation of UDP‐glucose to generate UDP‐glucuronate, but its roles and detailed regulatory mechanisms in cancer progression remain unclear. UGDH participates in tumour formation and cancer migration in breast cancer, colorectal carcinoma, glioblastoma and lung cancer 11‐14 . Previous studies also demonstrated that UGDH is regulated by transforming growth factor‐β pathway, including p38, extracellular signal‐regulated kinase (ERK), mitogen‐activated protein kinase (MAPK).…”
Section: Introductionmentioning
confidence: 99%
“…This process is known as the epithelial-mesenchymal transition (EMT) (8). Epithelial cancer cells in the lactiferous duct having undergone EMT are capable of undergoing metastasis and are more invasive (9)(10)(11). Transforming growth factor (TGF)-β1 has been reported to induce EMT (12).…”
Section: Introductionmentioning
confidence: 99%